Creation and Validation of the Interview Guide: A Qualitative Part of the Validation of the Basic English Examination Project - Adamova, K. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This paper describes the creation process of the interview guide creation and validation, which is one of the data collection tools for qualitative research design. The interview guide allows careful planning of the structure and content of the interview, that consequently may lead to getting deeper analysis within the amount and scope of information collected. To prepare a meaningful and insightful interview guide that covers all significant areas to be researched, it needs careful planning and preparation stage. The method implemented is based on two existing models for interview validation. The presented research portrays the process of interview guide design and formation, followed by a practical illustration of how, based on the existing framework, it can be validated and piloted for the research. It is important to mention that the major aim of the interview guide is to collect data for the qualitative part of the Basic English Examination and help to contribute to the validation process of this crucial assessment procedure from a broader perspective. Overall, the paper brings valuable insights into qualitative research and facilitates the effective production of the research tool or the improvement of the existing methodology.